Penegakan Hukum Terhadap Selebgram yang Mempromosikan Situs Judi Online di Indonesia: Analisis Legal Normatif - Inera Faren Arganesya; Prasetijo Rijadi (DE RECHT (Journal of Police and Law Enforcement), 2025)
The widespread use of social media platforms by influencers as a medium for promoting online gambling sites has become a serious concern within Indonesia's digital legal landscape. This study aims to analyze the positive legal framework governing the criminal act of online gambling promotion by instagram influencers, examine the forms of criminal liability that may be imposed, and identify the obstacles encountered in law enforcement. This study employs a normative legal method by examining primary legal materials comprising relevant legislation and court decisions, as well as secondary legal materials including legal literature and academic journals. The findings reveal that the act of promoting online gambling is expressly prohibited under Article 303 of the Criminal Code and Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of Law Number 1 of 2024 on Electronic Information and Transactions (UU ITE), carrying penalties of up to 10 years imprisonment and fines of up to  10 billion Rupiah. Criminal liability may be imposed upon influencers where the elements of actus reus and mens rea are established, whether through intentional conduct (dolus) or negligence (culpa). Nevertheless, law enforcement remains constrained by several structural and technical obstacles, including cross-border and anonymous transactions, limited digital forensic capacity, rapidly evolving criminal methods, low legal literacy among influencers, and slow responses from digital platforms. Gustav Radbruch's legal certainty theory, the current enforcement framework against influencers who promote online gambling has yet to meet the standard of legal certainty envisioned by the law, necessitating regulatory synchronization, strengthened inter-agency cooperation, and improved public legal literacy to foster a more orderly and just digital ecosystem.